2009
DOI: 10.1002/esp.1722
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model for the longitudinal distribution of wood in mountain streams

Abstract: Wood load, channel parameters and valley parameters were surveyed in 50 contiguous stream segments each 25 m in length along 12 streams in the Colorado Front Range. Length and diameter of each piece of wood were measured, and the orientation of each piece was tallied as a ramp, buried, bridge or unattached. These data were then used to evaluate longitudinal patterns of wood distribution in forested headwater streams of the Colorado Front Range, and potential channel-, valley-and watershed-scale controls on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 54 publications
6
131
1
Order By: Relevance
“…Dams formed by accumulations of large wood increase channel complexity and facilitate deposition of organic matter, thus providing a food source for numerous invertebrate species and contributing to nutrient cycling and retention Wondzell and Bisson 2003). The influence of wood in affecting stream morphology depends on the size of the stream and the size of the wood pieces (Bilby and Ward 1989;Marcus and others 2002;Wohl and Jaeger 2009). The function of LW in forming fish habitat, especially plunge and dammed pools, is strongly influenced by the location of the stream or reach within a given watershed (Richmond and Fausch 1995).…”
Section: Valued Functions Of Riparian Plant Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Dams formed by accumulations of large wood increase channel complexity and facilitate deposition of organic matter, thus providing a food source for numerous invertebrate species and contributing to nutrient cycling and retention Wondzell and Bisson 2003). The influence of wood in affecting stream morphology depends on the size of the stream and the size of the wood pieces (Bilby and Ward 1989;Marcus and others 2002;Wohl and Jaeger 2009). The function of LW in forming fish habitat, especially plunge and dammed pools, is strongly influenced by the location of the stream or reach within a given watershed (Richmond and Fausch 1995).…”
Section: Valued Functions Of Riparian Plant Communitiesmentioning
confidence: 99%
“…The relative importance of chronic LW inputs vs. episodic, disturbance-related inputs varies in time and space (Benda and others 2003b) and is reflected in wood distribution at multiple scales. In one of the few empirical studies to quantify the longitudinal distribution of instream LW, Wohl and Jaeger (2009) surveyed wood pieces in 50 contiguous stream segments, each segment 25 m in length (total surveyed length = 1250 m per stream) along 12 streams in the Colorado Front Range. Their results suggested that local valley and channel geometry, i.e., valley-bottom width, gradient, and sequence of channel changes, exerted a stronger influence on patterns of longitudinal wood distribution than either time since last forest disturbance or progressive downstream trends associated with larger drainage area.…”
Section: Valued Functions Of Riparian Plant Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant recruitment from upstream hillslopes coupled with episodic floods that cause bank erosion and transport capacity downstream could synergistically increase upstream rate of export while decreasing the export rate with downstream changes to the floodplain dynamics (Marcus et al 2002;Reeves et al 2003;Seo and Nakamura, 2009;Wohl and Jaeger, 2009). …”
Section: Explanation 3 -No Significant Increase Of Recruitmentmentioning
confidence: 99%
“…A watershed approach to large wood dynamics is valuable for understanding the multi-scale drivers of large wood and connectivity among watersheds (Wohl and Jaeger, 2009). However, quantifying the large-scale patterns of large wood export is hampered by the highly variable and discontinuous recruitment and transport of large wood during high flow events (Moulin and Fremier, Seo and Nakamura Revised Manuscript -October 4, 2009 Page 5 of 39 Piégay, 2004;Comiti et al, 2006;Young et al, 2006).…”
Section: Introductionmentioning
confidence: 99%